Development JEJAKATUA Using Auto-Stitching as a Campus Virtual Tour to Support Digital Promotion Media - Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo (Nusantara Science and Technology Proceedings, 2020)
In the current millennial era, the digitalization of promotions offers abundant potential so that each agency is competing to attract public attention through the development of promotional digitization. East Java "Veteran" National Development University has the same opportunity to compete in providing the best digital information and promotions. As for some urgency to immediately build a campus network, it needs to be developed, prospective new students, prospective work partners, or colleagues who come from outside the city, outside the region, or even abroad, a distance appropriate to the cost becomes an obstacle to realizing the journey to campus, and the need provide real experiences and deeper impressions for the stakeholders to see the contents of the Campus. So, this study aims to build a Virtual Campus Exploration application (Jejakatua) as a Media Promotion Era at the "Veteran" National Development University of East Java. The result of this research has succeeded in building JEJAKATUA and can facilitate the limitations of distance, space, time, and costs for all Campus stakeholders in a more real, realistic, and interactive virtual form.